Assessing Population Administration Service Quality in Rural Settings - Aini, Muwaffiq Lailatul; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2023)
This qualitative study investigated the quality of administrative services in Desa Popoh, Wonoayu District, Sidoarjo Regency, Indonesia, addressing prevalent issues such as slow service delivery, uncertainty in completion timelines, unfamiliarity with procedural mechanisms, and perceived inadequacies in employee attitudes. Employing descriptive qualitative research methods, data were collected through interviews, observations, and documentation involving a service head and two service users. Findings revealed a relatively favorable assessment across indicators: Reliability, Responsiveness, Assurance, Empathy, and Tangibles, suggesting a reasonably good quality of service provision in the studied rural community. This study contributes insights into the factors influencing and hindering public service delivery, indicating a need for sustained efforts to enhance service efficiency and user satisfaction in similar settings. Highlights: Service Quality Evaluation: Investigated multiple indicators—Reliability, Responsiveness, Assurance, Empathy, and Tangibles—to assess the quality of administrative services. Rural Service Provision: Explored challenges in service delivery, including slow response times, procedural uncertainties, and staff attitudes, within a rural Indonesian community. Enhancement Opportunities: Identified scope for improving service efficiency and user satisfaction, emphasizing the need for sustained efforts in similar rural settings. Keywords: Public Service Quality, Rural Communities, Administrative Services, Indonesia, Service Delivery